Fatigue in Covid-19 survivors: The potential impact of a nutritional supplement on muscle strength and function. (October 2022) - Galluzzo, Vincenzo; Zazzara, Maria Beatrice; Ciciarello, Francesca; Savera, Giulia; Pais, Cristina; Calvani, Riccardo; Picca, Anna; Marzetti, Emanuele; Landi, Francesco; Tosato, Matteo; ,; Steering Committee,; et al.
Summary: Background: Fatigue with reduced tolerance to exercise is a common persistent long-lasting feature amongst COVID-19 survivors. The assessment of muscle function in this category of patients is often neglected. Aim: To evaluate the potential impact of a daily supplementation based on amino acids, minerals, vitamins, and plant extracts (Apportal®) on muscle function, body composition, laboratory parameters and self-rated health in a small group of COVID-19 survivors affected by fatigue. Methods: Thirty participants were enrolled among patients affected by physical fatigue during or after acute COVID-19 and admitted to the post-COVID-19 outpatient service at Fondazione Policlinico Gemelli in Rome between 1st March 2021 and 30th April 2021. All participants were evaluated at first visit (t0) and at control visit (t1), after taking a daily sachet of Apportal® for 28 days. Muscle function was analyzed using hand grip strength test, exhaustion strength time and the number of repetitions at one-minute chair stand test. Body composition was assessed with bioelectrical impedance analysis (BIA). Laboratory parameters, including standard blood biochemistry and ferritin levels, were evaluated at the first visit and during the control visit. A quick evaluation of self-rated health, before COVID-19, at t0 and t1, was obtained through a visual analogue scale (VAS). Results: Participants aged 60 years and older were 13 (43%). Females represented the 70% of the study sample. Participants hospitalized for COVID-19 with low-flow oxygen supplementation represented the 43.3% of the study sample while 3.3% received noninvasive ventilation (NIV) or invasive ventilation. Hand grip strength improved from 26.3 Kg to 28.9 Kg ( p < 0.05) at t1 as compared to t0. The mean time of strength exhaustion increased from 31.7 s (sec) at t0 to 47.5 s at t1 ( p < 0.05). Participants performed a higher number of repetitions (28.3 vs. 22.0; p < 0.05) during the one-minute chair stand test at t1 as compared to t0. A trend, although not significant, in reduction of ferritin levels was found after nutritional supplementation (94.4 vs. 84.3, respectively; p = 0.01). The self-rated health status increased by at least 13 points (t0, mean 57.6 ± 5.86; t1, mean 71.4 ± 6.73; p < 0.05). Conclusions: After 28 days of nutritional supplementation with Apportal® in COVID-19 survivors affected by fatigue with reduced tolerance to exercise, we found a significant improvement in means of muscle strength and physical performance, associated with enhancement of self-rated health status between t0 and t1. Highlights: Assessment of muscle function in persons recovered from COVID-19 is often neglected. Nutritional supplementation may enforce muscle strenght and function in COVID-19 survivors affected by fatigue. Daily assumption of magnesium, zinc, arginine and carnitine can improve physical symptoms in the Long Covid. Management of physical symptoms may ameliorate self-rated health status in adult COVID-19 survivors.